2016
DOI: 10.1093/nar/gkw859
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing structure–function relationships of artificial and cancer-associated PARP1 variants by reconstituting TALEN-generated HeLaPARP1knock-out cells

Abstract: Genotoxic stress activates PARP1, resulting in the post-translational modification of proteins with poly(ADP-ribose) (PAR). We genetically deleted PARP1 in one of the most widely used human cell systems, i.e. HeLa cells, via TALEN-mediated gene targeting. After comprehensive characterization of these cells during genotoxic stress, we analyzed structure–function relationships of PARP1 by reconstituting PARP1 KO cells with a series of PARP1 variants. Firstly, we verified that the PARP1\E988K mutant exhibits mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 87 publications
(138 reference statements)
6
53
0
Order By: Relevance
“…On the one hand, mutations that impair PARP1 polymerase activity have been reported to increase the risk of different cancers. For instance, V762A leads to about 40% decrease of PARP1 polymerase activity, 41 which is associated with the increased risk of cancers such as esophageal, lung, gastric, prostate 41 and colorectal 34 cancer. On the other hand, the mutations reducing PARP1 polymerase activity have been found to cause cellular and clinical resistance to PARPis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, mutations that impair PARP1 polymerase activity have been reported to increase the risk of different cancers. For instance, V762A leads to about 40% decrease of PARP1 polymerase activity, 41 which is associated with the increased risk of cancers such as esophageal, lung, gastric, prostate 41 and colorectal 34 cancer. On the other hand, the mutations reducing PARP1 polymerase activity have been found to cause cellular and clinical resistance to PARPis.…”
Section: Discussionmentioning
confidence: 99%
“…4a, Supporting Information Table 1). 21,22,24,30,31,[33][34][35][36] Then we separately transfected them into RD-ES/KO2 cells and obtained their variants that stably expressed corresponding mutated proteins of PARP1 (Fig. 4b).…”
Section: E988k-parp1 Possesses the Capability To Bind Nad + Parpi Amentioning
confidence: 99%
“…Our group and others have shown that genotoxic stress conditions specifically induce the ADP-ribosylation of hundreds of proteins. These studies identified ARTD1/PARP1 and histones to be the main acceptors of ADPr under these conditions [11][12][13][14]. ARTD1 and ARTD2/PARP2 are considered the two main enzymes that "write" nuclear PARylation [2,3,9].…”
Section: Introductionmentioning
confidence: 99%
“…The PARP1-E988K and PARP1-L713F mutant proteins were investigated through their overexpression in the TALEN-generated PARP1 knock-out HeLa cells. PARP1-E988K delayed its recruitment and persisted longer at the site of DNA lesions and induced G2 arrest in the cell cycle [63]. The gain-of-function mutant PARP1-L713F promoted cell apoptosis, even in the absence of DNA damage induction [63].…”
Section: Biological Functions Of Parp1mentioning
confidence: 99%